2012
DOI: 10.1016/j.ijsu.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional haemodynamic monitoring: The value of SVV as measured by the LiDCORapid™ in predicting fluid responsiveness in high risk vascular surgical patients

Abstract: Only the SVV was an adequate predictor of fluid responsiveness in this cohort of high risk surgical patients. Whereas PPV and SPV may be obtained from the arterial trace, estimation of the SVV requires a cardiac output monitor which is able to convert an arterial pressure trace into an estimation of stroke volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…It is important to remember that the phasic signal detected from a cardiopulmonary interaction is a function of the intensity of the tidal volume and ITP change, of the method used to track a respirophasic SV change [53] and of the degree of hypovolemia (relative or absolute). In addition, one cannot assume that exaggerated cardio-pulmonary interaction is synonymous with fluid responsiveness and/or hypovelemia.…”
Section: Arterial Side or Stroke Volume Based Methodsmentioning
confidence: 99%
“…It is important to remember that the phasic signal detected from a cardiopulmonary interaction is a function of the intensity of the tidal volume and ITP change, of the method used to track a respirophasic SV change [53] and of the degree of hypovolemia (relative or absolute). In addition, one cannot assume that exaggerated cardio-pulmonary interaction is synonymous with fluid responsiveness and/or hypovelemia.…”
Section: Arterial Side or Stroke Volume Based Methodsmentioning
confidence: 99%
“…Despite the initial enthusiastic approach, LiDCOrapid failed to demonstrate a good correlation for SV values when compared with the PiCCO pulse contour [64] or transesophageal Doppler [65]. Regarding the ability of the LiDCOrapid-SVV to predict the fluid responsiveness, some studies performed in high risk vascular surgery [66] and in cardiac surgery [67] confirmed that this parameter is an adequate predictor of the CO response to fluid administration. LiDCOrapid was never used in GDT protocols in cardiac surgery but in obstetrics where the main advantages were less maternal hypotension and much less neonatal hypercapnia and hypoxemia in the GDT group than in the control group [68].…”
Section: Lidcorapid (Lidco Ltd Cambridge Uk)mentioning
confidence: 99%
“…SVV has been shown to be an adequate predictor of fluid responsiveness in various studies [40]. ΔVTI has been compared with Vigileo (Edwards Lifesciences, Irvine, USA) derived SVV with similar performance in a setting of liver transplantation and vasopressor support [4], though with normal systemic vascular resistance.…”
Section: Mechanical Ventilator Induced Intra-thoracic Pressure Changementioning
confidence: 99%